2020
DOI: 10.1177/1750458920978858
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Human Factors in the operating theatres during the COVID-19 pandemic

Abstract: One of the priorities at our large Operating Theatres Department is to support awareness and basic education of the multi-disciplinary teams in clinical Human Factors, to help build competence and capacity in healthcare towards a resilient system. From May 2019 until February 2020, our Human Factors Champions embarked on a project called Observation of Non-technical Skills and Teamwork in the operating theatres (ONSeT), to monitor and evaluate the benefits of local Human Factors education. In September 2020, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Several studies expressed increased “connection” [ 72 ], “collaboration” [ 39 , 70 72 ] and a “sense of camaraderie” [ 70 ] among teams during the pandemic as they “rallied together” [ 40 ] and “worked together toward a common goal” [ 70 ]. Traditional clinical hierarchies were also reported as less important during delivery of care [ 72 ], leading to enhanced team dynamics and coordination [ 73 ]. Three studies also highlighted the role of “peer support” [ 56 , 65 , 69 ] as co-workers provided reassurance and supported staff wellbeing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies expressed increased “connection” [ 72 ], “collaboration” [ 39 , 70 72 ] and a “sense of camaraderie” [ 70 ] among teams during the pandemic as they “rallied together” [ 40 ] and “worked together toward a common goal” [ 70 ]. Traditional clinical hierarchies were also reported as less important during delivery of care [ 72 ], leading to enhanced team dynamics and coordination [ 73 ]. Three studies also highlighted the role of “peer support” [ 56 , 65 , 69 ] as co-workers provided reassurance and supported staff wellbeing.…”
Section: Resultsmentioning
confidence: 99%
“…What was clear was that the included studies reported varying degrees of preparedness and adaptive capacity across the different healthcare services. For example, a number of studies reported how well organisations or the people who work in them “evolved” to make things work [ 39 , 54 , 81 ], while others reported extreme physical and emotional demands, leading to stress and burnout amongst healthcare workers and poor clinical care [ 37 , 39 , 43 , 65 , 69 , 73 ]. This discrepancy between resilient performance and physical and emotional burnout could be explained by the extensive use of short-term adaptations, rather than long-term innovation and system change [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These improvements can translate into improved team performance and safety, but they require strong leadership and a culture of error management rather than error aversion to ensure that stressors do not degrade performance [ 22 ]. Surgeons and surgical leaders should employ collaborative leadership to identify and mitigate stressors imposed by the COVID-19 pandemic as we enter yet another wave to ensure that improved teamwork translates into improved team performance and, ultimately, improved patient safety [ 24 ].…”
Section: Discussionmentioning
confidence: 99%